Effect of Self Made Intravaginal Progesterone Sponge on Fertility in Goat - Jangir, Tara Chand; Hitesh,; Pradeep,; Rahul,; Kumar, Sandeep; Pandey, Anand Kumar; Luthra , Ram Avtar (The Indian Journal of Animal Reproduction, 2023)
Comparative studies of intravaginal sponges containing three different doses of progesterone on estrous synchronization; fertility, fecundity and prolificacy of synchronized does by natural mating were conducted during the breeding season at Central Sheep Breeding Farm, Hisar. A total of 60 Beetal does selected randomly and divided into group I, II and III with 20 does in each, and subsequently intravaginal sponges containing 50, 100 and 150 mg P4 were inserted respectively for 14 days and an i/m injection of PMSG (@200IU/doe) was injected just after sponge removal in each doe. Effective number of animals remained 55 as 5 does dropped their sponges. Forty eight to sixty hrs after sponge removal, 14, 16 and 15 does from group I, group II and group III respectively were synchronized to estrus and subsequently hand mated individually with bucks of proven fertility. The fertility, fecundity and prolificacy per cent after synchronization of oestrus in group I, group II and group III was 78.57, 87.50 and 86.66; 128.57, 156.25 and 166.66; 163.63, 178.57 and 192.30 respectively. Eighteen animals (6 does from each group) selected randomly out of 60 animals for progesterone estimation. Blood samples were collected immediately before insertion of intravaginal sponges (day 0) and then subsequently on day 7, 14 after sponge insertion and 48 and 72 hrs after sponge removal. Progesterone concentration was above basal level in most of animals on day 0 in all the groups. Increase in plasma progesterone concentration (with in group) was recorded on day 7 and decreased on day 14 & 48 hrs after sponge removal. These changes were significant in group II & III while non-significant in group I. Progesterone concentration decreased non-significantly 72 hours after sponge removal in all the three groups. Significant difference in plasma P4 concentration was reported in between group I and group II & III on day 7 & 14.
Keywords: Synchronization; Estrogen-progesterone; PMSG; Fertility; Fecundity and Prolificacy